Development and Field Testing of a Long-Term Care Decision Aid Website for Older Adults: Engaging Patients and Caregivers in User-Centered Design. (27th November 2019) - Hoffman, Aubri S; Bateman, Daniel R; Ganoe, Craig; Punjasthitkul, Sukdith; Das, Amar K; Hoffman, Derek B; Housten, Ashley J; Peirce, Hillary A; Dreyer, Larissa; Tang, Chen; Bennett, Alina; Bartels, Stephen J
Abstract: Background and Objectives: Decisions about long-term care and financing can be difficult to comprehend, consider, and communicate. In a previous needs assessment, families in rural areas requested a patient-facing website; however, questions arose about the acceptability of an online tool for older adults. This study engaged older adults and family caregivers in (a) designing and refining an interactive, tailored decision aid website, and (b) field testing its utility, feasibility, and acceptability. Research Design and Methods: Based on formative work, the research team engaged families in designing and iteratively revising paper drafts, then programmed a tailored website. The field test used the ThinkAloud approach and pre-/postquestionnaires to assess participants' knowledge, decisional conflict, usage, and acceptability ratings. Results: Forty-five older adults, family members, and stakeholders codesigned and tested the decision aid, yielding four decision-making steps: Get the Facts, What Matters Most, Consider Your Resources, and Make an Action Plan . User-based design and iterative storyboarding enhanced the content, personal decision-making activities, and user-generated resources. Field-testing participants scored 83.3% correct on knowledge items and reported moderate/low decisional conflict. All (100%) were able to use the website, spent an average of 26.3 min, and provided an average 87.5% acceptability rating. Discussion and Implications: A decision aid website can educate and support older adults and their family members in beginning a long-term care plan. Codesign and in-depth interviews improved usability, and lessons learned may guide the development of other aging decision aid websites.